Dental erosion in restorative dentistry - Asaad, Yasmin M.; Alrashidi, Abdullah N.; Alanazi, Muhannad G.; Alahmari, Ali M.; Aljohani, Mahdi A.; Aljammaz, Wejdan A.; Mudhish, Halah A.; Aldossari, Wejdan M.; Alkarni, Amal F.; Aldosari, Gehan M.; Alkhayyal, Abdulrahman K. (International Journal Of Community Medicine And Public Health, 2023)
Over time, teeth undergo both physical and chemical changes that result in the wearing down and thinning of dental hard tissues. These changes include various forms of damage, including abrasion, attrition, abfraction, and erosion. Among these, dental erosion caused by acids has emerged as a significant concern in the field of dentistry. While the incidence of tooth decay has decreased, dental erosion has become more prevalent, largely due to shifts in dietary habits. Detecting erosion at an early stage is crucial because the process is irreversible. The diagnosis involves a thorough examination of the teeth to identify specific erosion characteristics. Both external and internal factors contribute to the occurrence of erosion, and even children are susceptible to it. Implementing preventive measures, such as educating patients, providing dietary advice, and employing fluoride therapy, plays a vital role in managing erosion. Treatment approaches vary depending on the severity of the erosion and may include techniques ranging from sealing and direct composite restorations to more extensive reconstructions involving ceramic restorations. It is important to emphasize that adequate preventive measures and regular follow-up are crucial for achieving long-term success in managing erosion.